Effects of yoga on cancer-related fatigue and global side-effect burden in older cancer survivors. Issue 1 (January 2015) - Sprod, Lisa K.; Fernandez, Isabel D.; Janelsins, Michelle C.; Peppone, Luke J.; Atkins, James N.; Giguere, Jeffrey; Block, Robert; Mustian, Karen M.
Abstract Background Sixty percent of cancer survivors are 65 years of age or older. Cancer and its treatments lead to cancer-related fatigue and many other side effects, in turn, creating substantial global side-effect burden (total burden from all side effects) which, ultimately, compromises functional independence and quality of life. Various modes of exercise, such as yoga, reduce cancer-related fatigue and global side-effect burden in younger cancer survivors, but no studies have specifically examined the effects of yoga on older cancer survivors. Objectives The purpose of this study was to assess the effects of a 4-week yoga intervention (Yoga for Cancer Survivors: YOCAS©®) on overall cancer-related fatigue, and due to its multidimensional nature, the subdomains of cancer-related fatigue (general, physical, emotional, and mental) and global side-effect burden in older cancer survivors. Materials and Methods We conducted a secondary analysis on data from a multicenter phase III randomized controlled clinical trial with 2 arms (standard care and standard care plus a 4-week YOCAS©® intervention). The sample for this secondary analysis was 97 older cancer survivors (≥ 60 years of age), between 2 months and 2 years post-treatment, who participated in the original trial. Results Participants in the YOCAS©® intervention arm reported significantly lower cancer-related fatigue, physical fatigue, mental fatigue, and global side-effect burden than participants in the standard care arm following the 4-week intervention period (p < 0.05). Conclusions YOCAS©® is an effective standardized yoga intervention for reducing cancer-related fatigue, physical fatigue, mental fatigue, and global side-effect burden among older cancer survivors.